2017
DOI: 10.1007/s10995-017-2356-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Peer Counseling and Breastfeeding Initiation and Duration: An Analysis of Minnesota Participants in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC)

Abstract: Background Peer counseling (PC) has been associated with increased breastfeeding initiation and duration, but few analyses have examined the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) model for peer counseling or the continuation of breastfeeding from birth through 12 months postpartum. Objectives Identify associations between Minnesota WIC Peer Breastfeeding Support Program services and breastfeeding initiation and continuation. Methods Retrospective analysis of observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…Our results are consistent with the results from the studies of McCoy et al (), Gross et al (), and Srinivas et al () regarding the impact of peer counseling on breastfeeding initiation and continuation. Social support for postpartum women plays a vital role in the decision made by mothers to continue breastfeeding.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with the results from the studies of McCoy et al (), Gross et al (), and Srinivas et al () regarding the impact of peer counseling on breastfeeding initiation and continuation. Social support for postpartum women plays a vital role in the decision made by mothers to continue breastfeeding.…”
Section: Discussionsupporting
confidence: 93%
“…The results showed the positive effect of peer counseling on breastfeeding initiation and continuation from birth to 12 months postpartum. They suggested that providing peer counseling for women, especially in populations that have problems with breastfeeding initiation and duration, can improve the mother and the child's health (McCoy, Geppert, Dech, & Richardson, ). Campbell, Wan, Speck, and Hartig () suggest that future studies include mothers without breastfeeding experience who are supported by peer counseling groups and mothers who do not use peer counseling groups to compare breastfeeding commencement and other related variables (Campbell et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, скрининг пациентов с участием женщин, младенцев и детей во время дородовой помощи является важным способом обеспечить грудное вскармливание для многих женщин и семей. Этот тип совместной работы помогает женщинам достичь своих целей в области грудного вскармливания [44].…”
Section: клинический менеджмент тандема грудного вскармливанияunclassified
“…Further, the impact of specific WIC BFPC program components on BF initiation and duration as has been relatively understudied. [22][23][24][25] Therefore, the purpose of this study was to compare the initiation and duration of BF at 30 days among mothers enrolled in an upstate New York WIC program from April 1, 2009 to March 30, 2011, who accepted a BFPC referral, and received different quantities and types of BFPC support (telephone, in-person, and/or mailings).…”
Section: Introductionmentioning
confidence: 99%